The Development of an Android-Based Continental Food Appetizer Processing and Presentation of E-Module - Wulandari, Desy; Sugeng, Bambang; Khumaedi, Muhammad (Journal of Vocational and Career Education, 2023)
The 21st century is a century where science and technology develop very quickly and sophisticatedly, therefore in the development of the 21st century, teachers must be able to utilize technology in learning which can form a creative, innovative, and competitive generation. This research aims to test the validity and reliability of the e-module based on expert assessment, test the e-module in improving student learning outcomes, and analyze the improvement of student learning outcomes regarding the use of the e-module. This research model applied ADDIE. The subjects of this research were 35 students of XI grade students in culinary program at SMK Negeri 1 Kudus. The research results showed that the Android-based e-module considered feasible by media experts and material experts with CVR results > 0.75. The use of e-modules in learning depicted an improvement in learning outcomes through the results of the t-test and N-gain test of 76.25%. Based on these results, Android-based e-modules were effectively applied in the learning process to improve student learning outcomes. Meanwhile, the practicality test of e-modules portrayed the percentage of user responses from teachers and students gained 85% and 82% so the e-module learning media was categorized as very practical to use in the learning process. Based on the research results, e-module developed had been declared feasible, practical, and effective to use in processing and serving appetizer dishes learning and could improve student learning outcomes.